Psychological profiles of anti-vaccination argument endorsement - Holford, Dawn L. (2023)
The proliferation of anti-vaccination arguments online can threaten immunisation programmes, including those targeting COVID-19. To effectively refute misinformed views about vaccination, communicators need to go beyond providing correct information and debunking of misconceptions, and must consider the underlying motivations of people who hold contrarian views. Drawing on a taxonomy of anti-vaccination arguments that identified 11 "attitude roots"-i.e., psychological attributes-that motivate an individual's vaccine-hesitant attitude, we assessed whether these attitude roots were identifiable in argument endorsements and responses to psychological construct measures corresponding to the presumed attitude roots. In two UK samples (total n = 1250), we found that participants exhibited monological belief patterns in their highly correlated endorsements of anti-vaccination arguments drawn from different attitude roots, and that psychological constructs representing the attitude roots significantly predicted argument endorsement strength and vaccine hesitancy. We identified four different latent anti-vaccination profiles amongst our participants' responses. We conclude that endorsement of anti-vaccination arguments meaningfully dovetails with attitude roots clustering around anti-scientific beliefs and partisan ideologies, but that the balance between those attitudes differs considerably between people. Communicators must be aware of those individual differences.